Trends of the burden of type 2 diabetes mellitus attributable to high body mass index from 1990 to 2019 in China - Wang, Jianglin; Zhou, Lingyun; Yin, Wenjun; Hu, Can; Zuo, Xiaocong (Frontiers in Endocrinology, 2023)
Background: This study aimed to investigate the temporal trends of the T2DM burden attributable to high BMI in China from 1990 to 2019 and to evaluate the independent effects of age, period, and cohort on the burden of T2DM attributed to high BMI. Methods: Data on T2DM burden attributable to high BMI from 1990 to 2019 were obtained from the Global Burden of Disease (GBD) Study 2019. Joinpoint regression model and age-period-cohort analysis were performed to calculate the trends of the T2DM burden attributable to high BMI. Results: In 2019, deaths and DALYs from T2DM attributable to high BMI in China were 47.53 thousand and 3.74 million, respectively, five times higher than in 1990. Furthermore, ASMR and ASDR in 2019 were 2.39 per 100,000 (95%UI: 1.12-3.90) and 181.54 per 100,000 (95%UI: 93.71-286.33), respectively, representing a 91% and 126% increase since 1990. In China, women previously had higher ASMR and ASDR than men, while the differences in ASMR and ASDR between the sexes were reversed in recent years. From 1990 to 2019, ASMR in women increased before 2004, then decreased from 2004 to 2015, and increased again after, with an overall AAPC value of 1.6%.The ASMR in men continued to increase, with an overall AAPC value of 3.2%. The ASDR continued to increase in men and women, with AAPCs of 2.2% and 3.5%, respectively. The age effect showed that the RR of mortality increased with age in both males and females, except for the 75-84 age group. The impact of the age on the DALY rate revealed a trend of first rising and then decreasing, peaking at 65-69 years. The effect of the period on the burden of T2DM attributable to high BMI increased from 1990 to 2019. The cohort effect generally showed a downward trend. Conclusion: The burden of T2DM attributed to high BMI in China increased substantially from 1990 to 2019, particularly in men. Therefore, there is an urgent need for gender- and age-based public health guidelines on prevention strategies, early diagnosis, and effective management of T2DM, overweight, and obesity in China.